2018
DOI: 10.1016/j.ultsonch.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of crude oil pretreatment using low-frequency ultrasonic waves

Abstract: In this work, an ultrasound experimental setup was designed to investigate the feasibility of using low-frequency ultrasonic waves as a substitute to reduce the consumption of chemical demulsifiers in the pretreatment of crude oil. The experiments were planned to study the effects of irradiation time, ultrasonic field intensity and initial water content on the efficiency of separation. The results of experiments showed that by selecting a proper irradiation time and field intensity, it is possible to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In addition, emulsions could lead to clogging, corrosion and erosion in pipelines during transportation and the poisoning of catalysts in the refining process [16] , [17] , [18] , [19] , [20] , [21] , [22] . Hence, there are many studies that have been reported on the demulsification of crude oil [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] .…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, emulsions could lead to clogging, corrosion and erosion in pipelines during transportation and the poisoning of catalysts in the refining process [16] , [17] , [18] , [19] , [20] , [21] , [22] . Hence, there are many studies that have been reported on the demulsification of crude oil [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] .…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiesmentioning
confidence: 99%
“…The approaches that have been pursued in the demulsification process includes biological [23] , [24] , [25] , chemical [26] , [27] , [28] , [29] , [30] , [31] and physical [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] separation processes. Although biological separation through bacteria or synthetic agents provides better environmental benefits when compared to chemical demulsifiers, the separation process takes significant amount of time that could disrupt oil production.…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that a demulsification efficiency of 65% was attained by low-frequency ultrasound. Khajehesamedini et al [147] also reported the use of low-frequency ultrasonic waves for the demulsification of crude oil emulsions. They attained a demulsifying efficiency of 50% at a very low frequency, low irradiation time, and high-intensity ultrasonic waves.…”
Section: Ultrasonic Demulsificationmentioning
confidence: 99%
“…The small size of the aphron's bubbles provide them with high inter-facial areas that makes them amenable to being pumped, in a similar way to water, without risk of collapse [3]. A broad range of novel technologies and their applications, introduced in recent years, play a substantial role in improving standards of living and access to energy and resources, such as oil pretreatment [4,5], biofuels [6][7][8][9], corrosion [10,11], carbon dioxide [12][13][14], wastewater treatments [15,16], flow in porous media [17][18][19], bioresource technology [6][7][8]13,15,[20][21][22][23][24], Enhanced Oil Recovery [25][26][27][28][29][30]. CGA-based fluid technologies are being deployed with success in horizontal and high-angle wellbore trajectories in highly pressuredepleted reservoirs [31].…”
Section: Introductionmentioning
confidence: 99%